Kriminalisasi terhadap Pelanggaran Kewajiban Pelaku Usaha Mencantumkan Keterangan Tidak Halal pada Produk - Adismana, Oktaviana Hardayanti; Akub, Syukri; Burhamzah, Oky Deviany (Universitas Negeri Malang, 2022)
This study analyzed the criminalization and punishment of violations over Article 26 paragraph (2) of the Halal Product Guarantee Act. The approach used in this study was a statutory approach and a case approach with a normative juridical type of research. The data collection technique used in this study was a literature study. Data were analyzed using descriptive techniques. The results indicated that criminalization of violations over Article 26 paragraph (2) of the Law on Halal Product Guarantees could be carried out because violations over the obligation of businesspeople to include non-halal information on products could be categorized as criminal acts and include types of crime. Criminal sanctions were used as the final sanction for prevention purposes. The penalty for violating Article 26 paragraph (2) of the Law on Halal Product Guarantee was subject to criminal sanctions in confinement, fines, or imprisonment.